GUA KIDANG, PILIHAN MANUSIA PRASEJARAH DI KAWASAN KARST BLORA - Indah Asikin Nurani; J. Susetyo Edy Yuwono (Berkala Arkeologi, 2008)
Blora karst area is a part of Rembang karst area on its northern and southern side of Kendeng Mountain. Geographically as well as geologically, Blora karst area is similar to Tuban karst area, but from archaeological aspect both areas show a significant difference. Tuban karst area is rich with various artifacts and ecofacts from prehistoric caves in particular. Meanwhile, in Blora there is one only cave showing evidences as a prehistoric dwelling place, which is Kidang cave. This cave is important because it shows a specific character compared to other caves in Java.